Термодинамические исследования ферритов бария - Шабанова, Галина Николаевна; Быканов, Сергей Николаевич; Гуренко, Ирина Викторовна; Дейнека, Виктория Владимировна; Ткачева, З. И.; Корогодская, Алла Николаевна; Пермяков, Ю. В. (Национальный технический университет "Харьковский политехнический институт", 2006)
У статті наведено результати термодинамічно стабільних феритів барію. Створено базу термодинамічних даних: ентальпій, ентропій та коефіцієнтів рівняння теплоємності, необхідних для дослідження багатокомпонентних систем, до складу яких входять ферити барію.

The results of researches of thermodynamically stable barium ferrites are given. The base of the thermodynamic data (enthalpies, entropies and equation factors of the thermal capacity) which are necessary for research of the multycomponent systems with barium ferrites in their composition is created.
Keywords: теплоемкость; температура; феррит бария; термодинамические расчеты; энергия Гиббса; синтез